New substitute name Attenboroughctena nom. nov. for the genus Ceroctena Carré & Carré, 1991 (Ctenophora: Cydippida: Pleurobrachiidae) - Ceccolini, Filippo; Cianferoni, Fabio (Zootaxa, 2020)
Attenboroughctena Ceccolini & Cianferoni nom. nov. is established as the new name for the genus Ceroctena Carré & Carré, 1991 (Ctenophora: Cydippida: Pleurobrachiidae), preoccupied by Ceroctena Guenée, 1852 (Insecta: Lepidoptera: Noctuidae).